1985
DOI: 10.1007/bf01966596
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical mechanisms in 5-hydroxytryptamine-induced human platelet aggregation

Abstract: The activation of human platelets by 5-hydroxytryptamine (5-HT) is not accompanied by detectable release of ATP or TXB2. The process is unaffected by cyclooxygenase, thromboxane synthetase or combined cyclooxygenase/lipoxygenase inhibition (suprofen, indomethacin, R 19091, dazoxiben, N.D.G.A, BW755C, esculetin), indicating the absence of involvement of arachidonic acid metabolites. Transmembrane Ca2+-entry blockers (flunarizine, nifedipine, nimodipine) have no effect either, indicating that the activator calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In the human platelet, 5-hydroxytryptamine induces shape changes and reversible aggregation without secretion [45]; the cellular free Ca2+ concentrations are raised [4]. Previous reports [4,46] showed that these phenomena were inhibited by PGE1 and FK in the concentration range in which they inhibit 5-hydroxytryptamine-induced increases in 40 kDa-and 20 kDaprotein phosphorylation and PA formation (Fig. 1).…”
Section: Discussionmentioning
confidence: 79%
“…In the human platelet, 5-hydroxytryptamine induces shape changes and reversible aggregation without secretion [45]; the cellular free Ca2+ concentrations are raised [4]. Previous reports [4,46] showed that these phenomena were inhibited by PGE1 and FK in the concentration range in which they inhibit 5-hydroxytryptamine-induced increases in 40 kDa-and 20 kDaprotein phosphorylation and PA formation (Fig. 1).…”
Section: Discussionmentioning
confidence: 79%
“…One of the many factors which stimulate platelet aggregation is serotonin [7,8]. It amplifies platelet aggregation of rats and hu mans via 5-HT2 receptors [7,8], of which a selective antagonist is ketanserin [14], Thus we tried to determine whether the serotoner gic mechanisms play any role in the suppres sion of platelet aggregation evoked by capto pril.…”
Section: Discussionmentioning
confidence: 99%
“…It amplifies platelet aggregation of rats and hu mans via 5-HT2 receptors [7,8], of which a selective antagonist is ketanserin [14], Thus we tried to determine whether the serotoner gic mechanisms play any role in the suppres sion of platelet aggregation evoked by capto pril. In our experiments we demonstrated that captopril, in contrast to ketanserin, did not affect the amplifying effect of 5-HT ( fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that ethanol directly affects the function of blood platelet mem branes and acts indirectly by influencing plasma lipids or by changing the release and synthesis of some arachidonic acid deriva tives [2,5,6). Platelets contain serotonin (5-hydroxytryptamine, 5-HT) which evokes in vitro a reversible aggregation of human blood platelets [7] and amplifies platelet ag gregation in response to various agonists in cluding ADP, adrenaline, noradrenaline, collagen and the calcium ionophore A23187 [8], The amplification of platelet aggrega tion by 5-HT is inhibited by the selective 5-HT2 receptor antagonist ketanserin [9], Our previous studies demonstrated [10] that eth anol inhibits the uptake and enhances the release of 5-HT from rat blood platelets. In vitro, it inhibited the aggregation of blood platelets but did not change the potentiating action of 5-HT on ADP-induced aggrega tion.…”
Section: Introductionmentioning
confidence: 99%